Fake/Bogus Conferences: Their Features and Some Subtle Ways to Differentiate Them from Real Ones. - Asadi, Amin; Rahbar, Nader; Rezvani, Mohammad Javad; Asadi, Fahime (Science & Engineering Ethics, 2018)
The main objective of the present paper is to introduce some features of fake/bogus conferences and some viable approaches to differentiate them from the real ones. These fake/bogus conferences introduce themselves as international conferences, which are multidisciplinary and indexed in major scientific digital libraries. Furthermore, most of the fake/bogus conference holders offer publishing the accepted papers in ISI journals and use other techniques in their advertisement e-mails.